Feasibility of Fibroscan in Assessment of Hepatic Steatosis and Fibrosis in Obese Patients: Report From a General Internal Medicine Clinic - Avcu, Ayşegül; Kaya, Eda; Yilmaz, Yusuf (Turkish Journal of Gastroenterology, 2021)
Background: In metabolic associated fatty liver disease (MAFLD) vibration controlled transient elastography (VCTE) by Fibroscan hasemerged as a non-invasive diagnostic tool for the measurement of controlled attenuation parameter (CAP) and liver stiffness measurement(LSM), which are surrogate markers for hepatic steatosis and fibrosis, respectively. However, obesity constitutes a limitation interms of creating unreliable examinations due to increased skin to liver capsule distance. Here, we aimed to investigate the feasibility ofVCTE in the evaluation of hepatic steatosis and fibrosis in obese individuals.Methods: A total of 126 consecutive obese patients (body mass index ≥30 kg/m2) without a known history of MAFLD enrolled in thestudy. We performed CAP and LSM measurements and calculated Fibrosis-4 Index for each patient and included data of those patientsto the analysis, from whom valid measurements were able to be taken.Results: Reliable VCTE measurements were able to be obtained in 122 patients (97%), from those in 34 patients with M and 88 patientsin XL probe (median age: 50 [18-75], 45 males and 77 females). In 1 patient VCTE failed to take any measurements and in 3 the measurementswere classified as unreliable. The mean CAP value was 323 ± 48 dB/m and the median LSM value 5.3 [1.8-34.3] kPa.Conclusion: CAP and LSM assessments by Fibroscan are reliable diagnostic tools for the early diagnosis of hepatic steatosis and fibrosisin obese individuals.